EFFECT OF 8-WEEK CONTINUOUS AEROBIC EXERCISE ON BODY COMPOSITION OF MALE ADOLESCENT STUDENTS IN DAWAKIN KUDU, KANO STATE (Wudil Journal of Science and Technology Education, 2025)
Several epidemiological studies have shown an inverse relationship between the level offitness and cardiovascular risk profile in adult population and have also reported thatendurance training in this population can reduce the risk factors. The objective of this studywas to determine the effect of eight week continuous aerobic exercise on body compositionvariables of male adolescent secondary school (SS) students of G.S.S. Yankatsari, DawakinKudu (DKD) Local Government Area (LGA), Kano State. Population consisted of all theadolescent boys between the ages of 14-18years (n =1,200) in G.SS Yankatsari DKD. 60male adolescent were randomlysampled and assigned into A&B 30 each. Group weresubjected into 8-weeks continuous aerobic exercise (n=30) which is low training modes, ofcontinuous aerobic exercise. it preceded by warm up activities including running, jumps, sideStretch, waist bend, and brisk walking with a view to elevate the body temperature andphysiological functions. while B group (n=30) as control. Anthropometric profiles measuredwere % BF, FP and LBM. null hypotheses were formulated and tested at an alpha level of0.05. Analysis of Variance One way (ANOVA) determined the significant differences betweenthe 2 groups. Result revealed that 8-week continuous aerobic exercise elicited significantchanges in body composition by improving (reduced) % BF of the Experimental group from(9.4105±2.14to 5.49±1.39), it also significantly changes body composition by improving(decreased) the body FP of the Experimental group from (41.7435±.18 to 41.4160±108) andimprove LBM (42.13±7.99 to 41.7±18) compared to control group. Kano State ministry ofEducation should collaborate with Health professionals and exercise scientiststo help createadditional services to adolescent students in schools with a view to engage in exercises formaintaining desirable body composition which can lead to healthier living.
Keywords: Continuous Aerobic Exercise, Body Composition, Male Adolescent